Lower limb deep vein thrombosis in first trimester pregnant woman. A case report - Ramírez-Calderón, Fanny (2018)
Venous thromboembolism represents a prominent cause of maternal morbidity and mortality with an incidence of 0.5 to 2.2 out of 1 000 pregnancies. Pregnant patients have 5 times increased risk compared with non-pregnant women; it is the second cause of death in this population. We present the case of a 27-year-old pregnant woman with 11 weeks of gestation with no significant history who was admitted to the Emergency Department due to 24 hours of pain, increased volume of the lower limb and slight functional impotence for walking. Venous Doppler ultrasound of the lower limbs revealed deep vein thrombosis of the left lower limb. The diagnosis and management of deep vein thrombosis during pregnancy and the need for timely recognition are discussed.